2016
DOI: 10.1016/j.ijid.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

HIV and aging

Abstract: With the wider availability of antiretrovirals, the world's HIV population is aging. More than 10% of the 34.5 million HIV-positive individuals worldwide are over the age of 50 years and the average age continues to increase. In the USA more than 50% of the 1.3 million people with HIV are over 50 years old and by the year 2030 it is estimated that 70% will be over the age of 50 years. Although the life expectancy of HIV-positive people has increased dramatically, it still lags behind that of HIV-negative indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
172
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(182 citation statements)
references
References 105 publications
(120 reference statements)
5
172
0
5
Order By: Relevance
“…Several studies have suggested that people living with HIV infection (PLWH) are at increased risk for chronic kidney disease (CKD) with a multifactorial pathogenesis . While the use of combination antiretroviral therapy (cART) as the standard of care in HIV infection has resulted in a decreased incidence of HIV‐associated nephropathy, it has also lengthened life expectancy, accompanied by an increased incidence of age‐related diseases, such as CKD .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested that people living with HIV infection (PLWH) are at increased risk for chronic kidney disease (CKD) with a multifactorial pathogenesis . While the use of combination antiretroviral therapy (cART) as the standard of care in HIV infection has resulted in a decreased incidence of HIV‐associated nephropathy, it has also lengthened life expectancy, accompanied by an increased incidence of age‐related diseases, such as CKD .…”
Section: Introductionmentioning
confidence: 99%
“…HIV nephropathy has decreased with the use of anti-retroviral therapy. Yet, in populations of PLWH, compared to uninfected peer groups, risk factors for kidney disease were present in our models including diabetes for HIV uninfected patients and hypertension for HIV patients [23]. Other studies have also revealed that kidney-related comorbidities are associated with extremely high medical-related costs, as indicated in both our models as top contributors to high Charlson scores [27].…”
Section: Discussionmentioning
confidence: 80%
“…HIV patients are recognized to be at high risk for cardiovascular-related illness, with heart disease being a very common complication [23]. Interestingly, both models included cardiovascular related illnesses: hypertension (HIV+) and heart failure (HIV-) were top significant contributors in both groups [23]. Higher rates of hypertension are observed in PLWH in addition to associated illnesses [28, 29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, numbers of HIV-infected people over the age of 50 increased dramatically in recent years (Wing, 2016). Consequently, as the HIV-infected ART-treated population ages, patients will be prone to age-related neurodegenerative disorders such as Alzheimer’s disease (AD) and Parkinson’s disease (PD).…”
Section: Introductionmentioning
confidence: 99%